The absence of urban planning in Lima from Ricardo Palma’s tradition «Un cerro que tiene historia» («A hill that has history»): a social and architectural reading - Pérez Sosa, Álvaro Adrián (2023)
The main objective of this article is to address the absence of urban planning and of a complete study of the topographic context in the construction industry in Lima, which leads to various problems that directly affect the buildings and their inhabitants. There is a record of this problem since the Viceroyalty period with the overflowing of rivers and it extends to contemporary times with an increase in the number of victims due to accelerated demographic growth and a deficient or non-existent soil study. The background on which this research will be based goes back to the times of the recently founded Ciudad de los Reyes, an urban center characterized by its sandy topography on which several constructions were carried out without taking into account this characteristic and, mainly, without carrying out a correct urban planning, which has resulted in unstable foundations, prone to collapse or be terribly affected by any disaster.